SPS606 : Motor control and learning / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2018)
This course provides students with an overview of neural mechanisms underlying human movement. The approach is on behavioural and neurphysiological process to understand the acquisition and execution of motor skills.